ANALISIS KOMPETENSI SOSIAL DAN KESIPLINAN TERHADAP KINERJA GURU DENGAN IKLIM ORGANISASI SEBAGAI VARIABEL MODERASI - Santosa, Agus Budi; Kristiana, Ekowati (Proceeding SENDI_U, 2019)
Education is a tool to develop the quality of a country. Generally, the development of a country cannotbe separated from the development of a country. The government has attempted so many policies in order toimprove the condition of education and develop our education quality. Teachers’ performance at school hascrucial part in reaching school’s goal. Thus, teachers should be really competent in their field and perform theirrole optimally. This research aimed to analyze the organizational climate in modernizing social competency anddiscipline toward teachers’ performance at SMP N on Juwana District, Pati Regency. This research type is fieldresearch by using quantitative approach. The population in the research were 140 civil servant teachers. Thesample was taken by using purposive random sampling technique. Data analysis technique was started frominstrument test, normality test, multicollinearity test, hetetoscedasticity test, model test, hypothesis test, andmoderation test. The research results showed that independent variable, such as social competency, discipline,and organizational climate influenced teachers’ performance. Meanwhile, organizational climate variablemodernized the influence of social competency and discipline toward teachers’ performance.